Intrauterine growth pattern in Butajira HDSS, Southern Ethiopia: BUNMAP pregnancy cohort - Yalemwork G. Mengistu; Damen Hailemariam; Meselech A. Roro; Bilal S. Endris; Kokeb Tesfamariam; Seifu H. Gebreyesus (BMC, 2023)
Abstract Background Abnormal fetal growth pattern during pregnancy including excessive fetal size and intrauterine growth restrictions are the major determinants for perinatal outcomes and postnatal growth. Ultrasonography is a useful tool in monitoring fetal growth for appropriate care and interventions. However, there are few longitudinal studies using serial ultrasonography in low and middle-income countries. Moreover, the reference charts used for fetal growth monitoring in low-income countries comes from high income countries with distinct population features. Therefore, the purpose of this study was to evaluate the intrauterine growth pattern of the fetus using serial ultrasonography. Methods We conducted a prospective community-based cohort study from March 2018 to December 2019. Pregnant women with gestational age of 24 weeks or below living in the Butajira HDSS were enrolled. We followed the pregnant women until delivery. Serial ultrasound measurements were taken, and fetal weight was estimated using the Hadlock algorithm based on biparietal diameter, head circumference, abdominal circumference, and femur length. The z-scores and percentiles of biometric measurements were calculated and compared to the INTERGROWTH-21st International Standards for Fetal Growth. Results We reviewed a total of 2055 ultrasound scans and 746 women who fulfill the inclusion criteria were involved". We found similar distribution patterns of biometric measurements and estimated fetal weight compared to the previous study done in Ethiopia, the WHO and INTERGROWTH-21st references. In our study, the 5th,50th and 95th percentiles of estimated fetal weight distribution have a similar pattern to the WHO and INTERGROWTH-21st charts. The 50th and 95th percentile had also a similar distribution pattern with the previous study conducted in Ethiopia. We found that 10% of the fetus were small for gestational age (below the 10th percentile) based on the Z-score of estimated fetal weight. Conclusion Our study evaluated the fetal growth patterns in rural community of Ethiopia using serial ultrasound biometric measurements. We found similar IUG patterns to the WHO and INTERGROWTH-21st reference standards as well as the previous study conducted in Ethiopia.